Tourism ventures in Capiz readings on festivals and heritage sites - Clavel, Virginia S.; Clavel, Nelson S. (Book Project Services for Family Saga in cooperation with Capeeth Research & Writing Institute, 2017)
"This volume contains readings on Capiz tourism. It features the annual Capiztahan festival and three of the province's defunct celebrative events, namely: Halran, Sinadya sa Halaran and Aswang Festivals. It also highlights two heritage sites in Roxas City - Barangay VI and Sitio San Juan in Barangay Baybay - which, if restored and/or developed, may become tourist attractions."--Preface.